Business Internationalization in the Wood Pellet Industry: Increasing Competitiveness in the Global Market - Bastomi, Mohamad; Sudarmiatin, Sudarmiatin (STKIP PGRI SITUBONDO, 2024)
This study aims to analyze business internationalization strategies in the sustainable wood pellet industry, specifically in facing challenges and taking advantage of opportunities in the global market. Business internationalization in this sector has become relevant given the increasing global demand for renewable energy. The study used the strengths, weaknesses, opportunities and threats (SWOT) analysis method to identify the main factors affecting the company's competitiveness in international expansion. The results of the analysis show that high product quality and sustainable raw materials are the company's competitive advantages, but limited production capacity and dependence on certain markets can be obstacles in the internationalization process. In addition, global competition and fluctuating raw material prices emerge as threats that need to be anticipated with risk mitigation strategies and operational efficiency. The practical implications of this study include recommendations for capacity building and market diversification, while its theoretical contributions enrich the literature related to MSME internationalization in the renewable energy sector. The study offers strategic perspectives to guide firms in developing sustainable global competitiveness in the wood pellet market.